Areas of Developing University Education in some Saudi Universities from the Point of View of Staff Members: A Field Study - Nawaf Abdulla ALrawaili (University of Science and Technology, Yemen, 2017)
The study aimed to identify areas of developing university education in some Saudi universities. The sample of the study was 1873 male Saudi PhD holders. A survey was developed to collect necessary information to achieve the objective of the study. The survey consisted of two parts. Part I: items about general information about the respondents. Part II: items about their responses regarding areas of the study. An interview form was also developed for interviewing five university leaders from some Saudi universities in order to extrapolate their opinions regarding university education in Saudi universities and the areas of development. The researcher used analytical descriptive methodology. The study results showed that revealed the most important areas for developing university education are the following: developing a common database of published scientific researches; supporting outstanding and talented students; developing academic programs; increasing the use of staff members' experience in community service; conducting on-going evaluation of programs; and applying standards of academic accreditation. Results of study showed significant statistical differences due to variable effect of university name for Umm Al-Qura University. There were no significant differences among the sample due to the nature of work and academic specialization regarding their evaluation and approval of the importance of the suggested areas to develop university education and the attempt to achieve them in their universities because of the positive effect on developing university education in Saudi Arabia.    Keywords: Higher education, University jobs, Total development, Objectives of university education, Factors effecting higher education development.